2001
DOI: 10.1046/j.1526-0968.2001.005002142.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Refractory Endocrine Ophthalmopathy Successfully Treated with Extracorporeal Immunoadsorption

Abstract: Endocrine ophthalmopathy (EO) is a severe disease entity that is characterized by retrobulbar swelling due to accumulation of glycosaminoglycans on an autoimmune basis. This disorder can lead to the loss of vision and often is resistant to conventional therapy. There is a relation to Graves' hyperthyroidism, but probably no close association. Two patients with severe EO that was resistant to usual therapeutic approaches including steroids and radiological and surgical measures underwent a 20 session course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Another publication described a beneficial effect of immunoapheresis in two cases of refractory TAO 13. At the 5th World Congress of the International Society for Apheresis (Rostock‐Warnemunde, May 4 to 7, 2005), the same group of researchers reported that immunoadsorption caused marked improvement of inflammatory signs in 5 patients.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Another publication described a beneficial effect of immunoapheresis in two cases of refractory TAO 13. At the 5th World Congress of the International Society for Apheresis (Rostock‐Warnemunde, May 4 to 7, 2005), the same group of researchers reported that immunoadsorption caused marked improvement of inflammatory signs in 5 patients.…”
Section: Discussionmentioning
confidence: 96%
“…Standard plasma exchange has several disadvantages (it is nonselective and there is a danger of allergic reactions and infection transmission after volume substitution with fresh frozen plasma) and is currently replaced by more selective and safer methods, for example, plasma filtration15 or immunoapheresis 13. We decided to use the plasma filtration technique because it has been proven to be effective in other autoimmune disorders, such as myasthenia gravis,17, 22 Guillain‐Barre's, and Fisher's syndromes,16 and for removal of ABO antibodies before renal transplantation 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of IL-6 can lead to a proliferation of hemaocytes, immunoresponse, inflammatory reaction, and an increase in the number of cells in the nervous system. In thyroid-associated ophthalmopathy, accumulation of glycosaminoglycan to orbital adipose tissue and connective tissue of the extraocular muscle is seen by histopathology along with lymphocyte permeation to the tissues (Prophet et al 2001), and there are some reports of a rise in the serum level of IL-6 at the same time (Wakelkamp et al 2000; Kozora et al 2001). IL-6 production can be controlled by steroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It often develops on the background of allergies and accompanies atopic dermatitis. In this case the conjunctiva, eyelids, cornea, and lacrimal glands are damaged [117][118][119]. They are characterized by micro erosions of the epithelium, persistent epithelial defects, severe corneal vascularization and opacities [120].…”
Section: Keratoconjunctivitismentioning
confidence: 99%